Historical, Doctrinal, and Empirical Insights into Latter-day Saint Sexual Minorities' Psychological and Interpersonal Functioning. Issue 2 (15th March 2021) - McGraw, James S.; Chinn, Jessica; Mahoney, Annette
Abstract: There is a growing need for culturally specific information regarding the intersections of religion, spirituality, and various sexual orientations/attractions. In this article, we attempt to provide clinicians, scholars, advocacy groups, and religious organizations with salient information regarding the psychological and interpersonal functioning of current and former members of the Church of Jesus Christ of Latter-day Saints (LDS) who identify as lesbian, gay, bisexual, questioning/queer, or are same-sex attracted (LGBQ/SSA). First, an overview of LDS historical events and doctrinal teachings related to LGBQ/SSA issues is presented to increase cultural competence specific to this population. Second, we provide a narrative review of the known empirical literature on this population (i.e., N  = 33 empirical articles and dissertations, which comprise a range of quantitative/mixed methods ( n  = 19) and qualitative ( n  = 14) studies. Finally, recommendations for practice and future research are offered.,